Reading comprehensively using an interactive-reflective writing technique: From theory to implementation - Yustinus Calvin Gai Mali (EduLite: Journal of English Education, Literature and Culture, 2026)
Reading and reflecting on an English literacy book with hundreds of pages, advanced vocabulary, and complex literacy theories might be daunting tasks for English as a Foreign Language (EFL) students. In response, this basic qualitative study aims to illustrate the implementation of the Interactive-Reflective Writing (IRW) technique for reading and reflecting on the textbook entitled Remixing Multiliteracies: Theory and Practice from New London to New Times, edited by Frank Serafini and Elisabeth Gee in 2017. To achieve that goal, the author collected supporting data, including the author’s reflection submitted to a literacy content course, the transcripts of his asynchronous written interactions with three graduate students, and the course instructor’s written feedback. The author then analyzed the data qualitatively and presented them to illustrate better how the IRW technique was implemented. In the results section, the author presented his reflections under five main themes: redefining teachers’ roles, using his blog to spread optimism, communicating in the real world, understanding the meaning of digital touch, and connecting classroom learning to students’ real life. With that, this paper provided some evidence on how the technique might help the author grasp and make personal connections to the ideas conveyed in the literacy book, explain the meanings of literacy in the twenty-first century, and identify areas for his future improvement as a person and an English teacher. It is hoped that the IRW technique will interest EFL lecturers worldwide seeking novel and creative ways to help their students comprehend a textbook with characteristics similar to those discussed in this study. In the end, the author acknowledged the study’s limitations and outlined directions for further research.